Software engineering Principles and practice - Vliet, Hans Van (John Wiley & Sons, 2008)
Software Engineering: Principles and Practice challenges the reader to appreciate the issues, design trade-offs and teamwork required for successful software development. This new edition has been brought fully up to date, with complete coverage of all aspects of the software lifecycle and a strong focus on all the skills needed to carry out software projects on time and within budget.